Information technology capabilities and firm performance: A study of medium-sized manufacturing enterprises in Pakistan / Nabeel Rehman - Nabeel , Rehman (2019)
The Small and medium enterprises (SMEs) of any country formulate an integral part of economic activities of that country and are considered as the backbone of not only for the developed countries but also for the developing ones. Despite of significant contribution of SMEs towards the economic development; these firms are facing high risk of failure and survival challenges, particularly in developing countries. The main reason for high failure rate is lack of knowledge about efficient utilization of information technology (IT) capabilities. That is way the contribution of SMEs in gross domestic products is gradually decreasing, particularly in manufacturing sectors SMEs of developing nations. In modern era of technology, IT capabilities are regarded as a tool for competitiveness for business organizations. However, the underlying mechanisms, through which IT capabilities affect performance outcomes are still not clear and needed to be explored further. In addition, the research on absorptive capacity and corporate entrepreneurship outcomes still lacks integrative examinations of innovation performance and firm performance measures. On the basis of the resource-based view and dynamic capability view, this study contributes to the current literature by empirically analyzing an integrated theoretical model that explains that how IT capability dimensions (IT infrastructure flexibility, IT technical skills, IT integration, and IT business alignment) unfold the SMEs performance outcomes such as innovation performance and firm performance. It also explains that how the relationship between these two variables is affected by intervention of absorptive capacity and corporate entrepreneurship. Hence, this study contributes towards literature by investigating the sequential mediation role of absorptive capacity and corporate entrepreneurship between different IT capability dimensions and SMEs performance outcomes. For the purpose, the data of 417 respondents has been collected from medium-sized manufacturing sector SMEs of Pakistan. This study employs a survey technique by using the cluster sampling approach. The respondents of this study are chief executive officers and senior management officials from medium-sized manufacturing firms of Pakistan. The direct and indirect relationship hypotheses have been analyzed through structural equation modeling (Smart-PLS). The findings of this study support all the direct relation hypotheses and also highlight that absorptive capacity and corporate entrepreneurship mediate all relationships between IT capability dimensions and SMEs performance outcomes. These results indicate that the dimensions of IT capability play a critical role in attaining the high level of innovation and firm performance. It has also been inferred from the findings that the firms also need to focus on the sequential role of absorptive capacity and corporate entrepreneurship. In the end, this study proposes potential avenues for future research regarding the firm performance and the role of IT in current business environment.